The effect of a ketogenic diet versus a high-carbohydrate, low-fat diet on sleep, cognition, thyroid function, and cardiovascular health independent of weight loss: study protocol for a randomized controlled trial - Iacovides, Stella; Meiring, Rebecca M. (BMC, 2018)
Background: Many physiological health benefits observed after following a ketogenic diet (KD) can be attributed to the associated weight loss. The KD has become more prominent as a popular health choice, not only in obese/overweight individuals, but also in healthy adults. The study aims to determine the effects of a KD, independent of weight loss, on various aspects of physiological health including: sleep, thyroid function, cognition, and cardio-metabolic health. The study will also aim to determine whether a change in basal metabolic rate may be associated with any changes observed. Methods: Twenty healthy men and women between 18 and 50 years of age will take part in this study. In a randomized controlled, cross-over design, participants will follow two isocaloric diets: a high-carbohydrate, low-fat diet (55% CHO, 20% fat, 25% protein) and a KD (15% CHO, 60% fat, 25% protein). Each dietary intervention will last for a minimum of 3 weeks, with a 1-week washout period in between. Before and after each diet, participants will be assessed for sleep quality, cognitive function, thyroid function, and basal metabolic rate. A blood sample will also be taken for the measurement of cardio-metabolic and immune markers. Discussion: The present study will help in understanding the potential effects of a KD on aspects of physiological health in healthy adults, without the confounding factor of weight loss. The study aims to fill a significant void in the academic literature with regards to the benefits and/or risks of a KD in a healthy population, but will also explore whether diet-related metabolic changes may be responsible for the changes observed in physiological health.
Keywords: High-fat; Low-carbohydrate; Ketogenic diet; Metabolism; Cognition; Thyroid function; Sleep; Healthy participants; SDG-3: Good health and well-being